2020
DOI: 10.3389/feart.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Change of Drought Characteristics in Mahaweli River Basin of Sri Lanka and the Associated Atmospheric Circulation Difference

Abstract: Understanding the spatiotemporal characteristics of drought at the river basin scale is vital for water resources management. In this study, the interdecadal variation of drought characteristics over the Mahaweli River Basin (MRB) in Sri Lanka was investigated for the 1985-2015 period, using the Standardized Precipitation Evapotranspiration Index (SPEI). Remarkable interdecadal change of yearly drought characteristics between 1985-1999 and 2000-2015 periods in the wet region of MRB can be found for mediumterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…According to Shelton and Lin [22], the streamflow in MRB largely depends on monsoon circulation. For instance, the western and southwestern parts of the MRB get rainfall mainly from the SWM, while the eastern and northern part receives adequate rainfall during the NEM season [60]. Therefore, we investigate the model performance for simulating the streamflow at the seasonal scale.…”
Section: Swat Model Skills To Simulate the Seasonal Streamflow In Mrbmentioning
confidence: 99%
“…According to Shelton and Lin [22], the streamflow in MRB largely depends on monsoon circulation. For instance, the western and southwestern parts of the MRB get rainfall mainly from the SWM, while the eastern and northern part receives adequate rainfall during the NEM season [60]. Therefore, we investigate the model performance for simulating the streamflow at the seasonal scale.…”
Section: Swat Model Skills To Simulate the Seasonal Streamflow In Mrbmentioning
confidence: 99%
“…van der Schrier et al (2011) suggested that this PET calculation method will not affect the observed variation of drought characteristics in the South Asian region. As further evidence, Lin and Shelton (2020) revealed that the method used for PET has not a strong influence on SPEI calculation for the Mahaweli River Basin in Sri Lanka. Bärring et al (2006) found a non-significant difference between the two results obtained using the observed area average with point observations for defining dry and wet spells.…”
Section: Standardized Precipitation Evapotranspiration Index (Spei)mentioning
confidence: 85%
“…The NEM season brings rain to the eastern part of the central highland, northern and eastern side of the island. Based on the regional differences in the rainfall amount, seasonality, and variability, the wet zone, intermediate zone, and the semiarid dry zone have been well-demarcated (Ranatunge et al 2003;Rubasinghe et al 2015;Malmgren et al 2003;Lin and Shelton 2020) as shown in Fig. 1a.…”
Section: Study Sitementioning
confidence: 97%
See 2 more Smart Citations